Weighted integral representations of harmonic functions in the unit disc by means of Mittag-Leffler type kernels - Hayrapetyan, Feliks (Armenian Journal of Mathematics, 2021)
For weighted L^p-classes of functions harmonic in the unit disc, we obtain a family of weighted integral representations with weight function of the type |w|^2φ·(1-|w|^2ρ)^β.